Exploring the Impact of Trust, Perceived Utility, Ease of Use Perception, and Social Influence on E-Payment Adoption - Lissa Rosdiana Noer; Jihan Fadhilah; Prahardika Prihananto; Bustanul Arifin Noer (JURNAL SOSIAL HUMANIORA (JSH), 2023)
Consumer behavior shifts from cash to digital transactions due to innovations in payment system digitization, primarily through electronic payments like mobile banking and electronic wallets. In Indonesia, Shopee Pay emerged as a prominent non-bank QRIS provider in 2021, with the Quick Response Code Indonesia Standard (QRIS) mandated for all payment service providers. QRIS usage potential is high in East Java, particularly in Surabaya, where Generation Z constitutes the dominant user group for digital payments. To understand the factors influencing Generation Z's e-payment adoption, a study investigated the impact of payment mediums (Shopee Pay and mobile banking) on key variables: trust, perceived usefulness, perceived ease of use, social influence, intention to use, and actual usage of e-payment. Using Structural Equation Modeling (SEM) and Multi-Group Analysis (MGA) on 390 data points, the study revealed that trust, perceived usefulness, perceived ease of use, and social influence significantly influence intention to use, subsequently affecting actual e-payment usage. Furthermore, the study found that the effect of payment media on the relationship between trust and intention to use is notable only in mobile banking, whereas social influence's impact on intention to use is significant exclusively for Shopee Pay, as indicated by MGA results.